The growth in office take-up in Dublins suburbs: a product of occupiers' changing locationaf criteria? - Bertz, Sunnhild (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
This paper addresses thc role which user-demand has played in influencing the viability of large-scale suburban office development in Dublin. particularly at new suburban locations. It is based on a wider study of the changing geography of office development in the city since the mid-l990s and the relative influence of changing planning contexts, the operations of dcvelopment interests and the changing locational criteria of users.
Keywords: Urban geography -- Ireland